Four-Year Follow-Up of Transient Ischemic Attacks, Strokes, and Mimics. Issue 5 (May 2015) - Dutta, Dipankar; Bowen, Emily; Foy, Chris
<x xml:space="preserve">Abstract</x> Background and Purpose— There is limited information on outcomes from rapid access transient ischemic attack (TIA) clinics. We present 4-year outcomes of TIAs, strokes, and mimics from a UK TIA clinic database. Methods— All patients referred between April 2010 and May 2012 were retrospectively identified and outcomes determined. End points were stroke, myocardial infarction, any vascular event (TIA, stroke, or myocardial infarction), and all-cause death. Data were analyzed by survival analysis. Results— Of 1067 patients, 31.6% were TIAs, 18% strokes, and 50.4% mimics. Median assessment time was 4.5 days from onset and follow-up was for 34.9 months. Subsequent strokes occurred in 7.1% of patients with TIA, 10.9% of patients with stroke, and 2.0% of mimics at the end of follow-up. Stroke risk at 90 days was 1.3% for patients diagnosed as TIA or stroke. Compared with mimics, hazard ratios for subsequent stroke were 3.88 (1.90–7.91) for TIA and 5.84 (2.81–12.11) for stroke. Hazard ratio for any subsequent vascular event was 2.91 (1.97–4.30) for TIA and 2.83 (1.81–4.41) for stroke. Hazard ratio for death was 1.68 (1.10–2.56) for TIA and 2.19 (1.38–3.46) for stroke. Conclusions— Our results show a lower 90-day stroke incidence after TIA or minor stroke than in earlier studies, suggesting that rapid access daily TIA clinics may be having a significant effect on reducing strokes.